Peran Sistem Informasi Pemasaran dalam Meningkatkan Penjualan pada PT. Machiko Jaya Indonesia - Ina Krissina Yuliani; Citra Savitri; Syifa Pramudita Faddila (Universitas Batanghari, 2023)
This study aims to determine the role of marketing information systems at PT. Machiko Jaya Indonesia. The type of method used in this research is descriptive qualitative with data collection techniques using data triangulation. PT. Machiko Jaya Indonesia is a manufacturing company located in the city of Bekasi that prod. uces products in the form of molds, dies, jigs, standard parts, conveyor machines, trolly, racks, etc. Marketing information systems have an important role in increasing sales, such as the system used by PT. Machiko Jaya Indonesia as a medium for establishing effective and efficient marketing strategies and facilitating managers in making decisions that affect sales increase. Problems were found in the promotion section, namely when the company's sales decreased due to erratic monthly income because there were no fixed contracts with customers so that when the work was finished, looking for the next job, the company needed to take advantage of social media as a form of promotion to introduce company products and reach more markets wider again